The potential impact of the aid for trade initiative - Page, Sheila (UN New YorkUS, 2007)
Discusses how the initiative arose, in the two contexts of development policy and international negotiations. Explores the decisions that now need to be taken and queries whether the initiative will mark a significant change in the aid or trade regimes.